Production process of papermaking black liquor silicone defoaming emulsion resistant to strong alkali and high temperature

CN122912784APending Publication Date: 2026-10-16SHANDONG YAXUN KANGDE FINE CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611113649.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

在碱热与机械剪切双重作用下,传统有机硅消泡乳液中的活性硅油核心、表面乳化剂体系以及固体核心粉体易产生水解或老化脱附,进而导致消泡剂发生大面积破乳、分层和析硅

Benefits of technology

1、造纸黑液有机硅消泡乳液在高温强碱环境下展现出良好的理化稳定性与消泡效能。通过在端羟基苯基聚硅氧烷中引入苯基并结合特定的保温反应,配合聚醚侧链的引入以及气相二氧化硅的偶联剂真空热处理,强化了活性主体在碱热条件下的抗分解能力与固体粉末的结合度。制得的乳液在强碱高温下恒温静置后,依然保持均匀乳液状态,无分层和析硅现象,表现出较好的理化稳定性;在原浆黑液体系中,其瞬时消泡速度较快、抑泡时间较长,改善了消泡剂在黑液提取段易破乳析硅和失效的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912784A_ABST
    Figure CN122912784A_ABST
Patent Text Reader

Abstract

The present application relates to defoaming agent preparation technical field, specifically to a kind of production process of papermaking black liquor organic silicon defoaming emulsion resistant to strong base high temperature.The present application overcomes the problem that defoaming agent is easy to break emulsion and silicon is lost in the high-temperature and strong-base environment of black liquor extraction section.The specific is that first hydroxyphenyl polysiloxane, hydrogen silicon oil and polyether monomer are subjected to addition reaction, then dimethyl silicone oil and fumed silica are introduced, and silane coupling agent is added for vacuum heat treatment;non-ionic surfactant is added to the oil phase, and the water phase prepared from deionized water, alkali-resistant surfactant and inorganic salt is subjected to two-stage controlled-speed reverse-phase emulsification, and then modified nano-cellulose stabilizer is added after high-pressure homogenization to mix uniformly.The emulsion produced has uniform particle size distribution, good physicochemical stability and anti-layering ability in alkaline and hot environment, fast defoaming speed and long-lasting bubble suppression, and has no interference to paper whiteness and breaking length, and good process compatibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of defoamer preparation technology, specifically to a production process for a silicone defoaming emulsion for papermaking black liquor that is resistant to strong alkali and high temperature. Background Technology

[0002] In the alkaline chemical pulping process, plant fiber raw materials, after being subjected to high-temperature, high-alkali chemical cooking, release and dissolve large amounts of natural surfactants such as lignin, resin soaps, and fatty acid soaps. During subsequent multi-stage extraction, extrusion, pulp conveying, and mechanical refining processes, intense mechanical shearing, agitation, and violent turbulence cause a large amount of air to be mixed into the pulp containing high concentrations of surfactants, resulting in the in-situ generation of continuous and stable alkaline high-temperature foam. This viscous foam not only severely reduces the efficiency of washing and waste liquor extraction equipment, causing pulp loss and overflow, but also hinders the uniform wetting and reaction of subsequent bleaching agents on the fiber surface. Therefore, in the post-pulping treatment process, a highly efficient defoamer must be continuously added to maintain normal production operation.

[0003] Currently, emulsion-type silicone defoamers composed of polysiloxane active substrates and inorganic solid fillers are widely used in industry. However, the black liquor system of the pulping extraction stage in papermaking is a harsh environment, typically characterized by high concentrations of free alkali, high shear forces, and high temperatures ranging from 110°C to 130°C. Under the combined effects of alkali heat and mechanical shear, the active silicone oil core, surface emulsifier system, and solid core powder in traditional silicone defoamer emulsions are prone to hydrolysis or aging and desorption, leading to large-scale demulsification, stratification, and silica precipitation of the defoamer. The free non-polar silicone oil droplets released after the failed demulsification aggregate, adhere to and coat the surface of the pulp fibers, severely hindering the improvement of paper whiteness in the bleaching stage. Furthermore, due to the blocking effect of the hydrophobic oil film, it destroys the active sites of hydrogen bonding between fibers, resulting in the deterioration of physical strength indicators such as breaking length of the final paper. Therefore, existing defoaming emulsions generally suffer from insufficient physicochemical stability, easy demulsification and failure, and technical defects that affect the quality of the final paper product under the high temperature and strong alkaline conditions of papermaking black liquor. Summary of the Invention

[0004] The purpose of this invention is to provide a production process for a silicone defoaming emulsion for papermaking black liquor that is resistant to strong alkali and high temperatures. This overcomes the problems of defoamers easily demulsifying and releasing silica and becoming ineffective in the high-temperature and strong alkaline environment of black liquor extraction.

[0005] To achieve the above objectives, the present invention provides the following technical solution: Hydroxyphenyl polysiloxane, tetramethyldihydrosiloxane, and anhydrous sodium acetate are added to the reactor. Stirring is started and the speed is set to 65-75 rpm. Under a nitrogen atmosphere, the system is heated to 95-105°C via jacketed heat transfer oil and refluxed for 170-190 minutes. The main reactor of this invention is equipped with a high-efficiency two-stage combined reflux condensation system. The first-stage condenser uses a shell-and-tube heat exchanger and is supplied with circulating cooling water at a temperature of 5-12°C (provided by the jacketed cooling water circulation pipeline 10). This is mainly used to trap and reflux the low-boiling-point, highly flammable tetramethyldihydrosiloxane monomer vapor. The second-stage condenser is connected to the distillation tail and is supplied with a cryogenic ethylene glycol aqueous solution at a temperature of -10 to -5°C to capture trace amounts of volatiles, ensuring that the reflux rate of the low-boiling-point components is greater than 99.5%. The entire reaction process is carried out under atmospheric pressure reflux, with a slight positive pressure maintained within the reactor at 0.01-0.03 MPa. By adjusting the continuous introduction flow rate of nitrogen gas with a purity ≥99.99% to 0.5-1.2 m³ / h. 3 h, calculated per 100 kg of terminal hydroxyl polysiloxane; a stable inert flow atmosphere is established within the reactor. During this condensation reaction, the silanol groups Si-OH and silane-hydrogen bonds Si-H undergo dehydrogenation condensation under the catalysis of anhydrous sodium acetate. The generated gas is mainly a mixture of inert diluted nitrogen and the byproduct hydrogen H2. The generated gas is collected and discharged through exhaust pipeline 8. An explosion-proof flame arrester and a high-sensitivity explosion-proof combustible gas graded alarm linkage system are installed in series on the exhaust pipeline. When the hydrogen concentration reaches 20% of the lower explosive limit, a level one alarm is activated and the nitrogen flushing rate is automatically increased. The exhaust gas is ultimately introduced into an anti-static high-altitude vent pipe or a nitrogen-filled high-altitude vent valve located outdoors for safe dilution and discharge. Accumulation in a closed workshop is strictly prohibited to meet the safety production standards for fine chemicals.

[0006] After the reaction is complete, the system is cooled to 75℃-80℃. Allyl polyoxyethylene polyoxypropylene ether is added to the reactor, nitrogen gas is continuously introduced, and a platinum complex catalyst with an effective platinum content of 3000ppm is added dropwise in portions. The temperature inside the reactor is controlled to not exceed 110℃ by using jacket cooling water. After the addition is complete, the reaction is maintained at 95℃-105℃ for 2.5h-6.0h until the infrared detection system reaches 2150cm². -1 The silane-hydrogen bond absorption peak disappeared. Cooling to 50℃-60℃ yielded a liquid of side-chain polyether and phenyl-modified polysiloxane, which remained directly in the original reactor.

[0007] Dimethyl silicone oil was added to the modified polysiloxane liquid, and the stirrer was started at 70-80 rpm. The system temperature was raised to 115-125°C. The vacuum level inside the reactor was controlled at -0.045 MPa to -0.055 MPa for 25-35 minutes. The fumed silica was intermittently drawn in three equal batches through the suction pipe, with intermittent stirring and mixing for 7-9 minutes after each batch. The stirring speed was then increased to 115-125 rpm, and γ-glycidyl etheroxypropyltrimethoxysilane coupling agent was added to the system. The reflux valve was closed, and the vacuum system was turned on, controlling the vacuum level inside the reactor at -0.080 MPa to -0.090 MPa. The temperature was raised to 145-180°C, and the reaction was allowed to proceed for 3.5 hours. After the reaction, the pressure inside the reactor was adjusted to atmospheric pressure and nitrogen was introduced for protection. The system temperature was then lowered to 60-70°C.

[0008] Add fatty alcohol polyoxyethylene ether AEO-3 to the heat-treated system, start the high-shear emulsification pump at the bottom of the reactor, set the shear speed to 2800 rpm-3000 rpm, and circulate the shear for 18 min-22 min to obtain the oil phase. In another auxiliary aqueous phase reactor, add deionized water, alkyl glycoside APG-0810 with a solid content of 50% and sodium metasilicate solid, stir and heat to 55℃-65℃ until completely dissolved to obtain the aqueous phase.

[0009] During the first stage of water addition, maintain the temperature inside the main reactor at 60℃-70℃, and operate the anchor stirrer at 95rpm-105rpm and the bottom high-shear pump at 2400rpm-2600rpm. For the first stage of water addition: pump 20% of the prepared aqueous phase into the oil phase reactor using a metering pump, controlling the water addition rate at 0.58% to 0.69% per minute based on the total mass of the aqueous phase, specifically at a feeding rate of 3.2kg / min-3.8kg / min. For the second stage of water addition: maintaining the stirring and shearing speeds, add the remaining 80% of the aqueous phase at 1.08% to 2.38% per minute based on the total mass of the aqueous phase, specifically at a pumping rate of 6.0kg / min-13.2kg / min. After all the aqueous phase has been added, continue high-shear circulation for 12min-18min to obtain a homogeneous pre-emulsion. Subsequently, pump this pre-emulsion into a two-stage high-pressure homogenizer for fine pulverization. The feed temperature of the pre-emulsion is controlled at 50-60℃, and the continuous feed flow rate of the homogenizer is controlled at 15-25L / min. Both the primary and secondary homogenizing valves of the two-stage high-pressure homogenizer adopt standard W-type impact ring valve cores that are resistant to strong alkalis and wear. The primary homogenizing pressure is set at 260-470 bar, and the secondary homogenizing pressure is set at 55-65 bar, with continuous homogenization cycles performed twice. During the continuous homogenization cycle, the material is cooled by an online plate heat exchanger. The interval between two cycles is controlled at 10-15 minutes, and the instantaneous temperature rise of the material after each homogenization is maintained below 15℃, ensuring that the median particle size D50 of the emulsion is within the range of 1.8μm to 2.5μm.

[0010] The homogenized emulsion was discharged into a finished product tank, and a modified nanocellulose aqueous dispersion with a solid content of 10% was added. The mixture was stirred at 55-65 rpm for 25-35 minutes. After the system was cooled to below 35°C, it was filtered through a 100-mesh pipe filter to obtain the organosilicon defoaming emulsion for papermaking black liquor.

[0011] A preferred method for producing modified nanocellulose aqueous dispersion is as follows: 125.0 kg of unmodified nanocellulose crystal (CNC) aqueous dispersion with a solid content of 8.0% is weighed and added to a modified reaction vessel equipped with a medium-speed stirrer and a temperature control jacket. Mechanical stirring is started and set to 180 rpm. 150.0 L of deionized water is added for dilution, and stirring is continued for 30 min to allow the nanocellulose crystals to fully depolymerize in the aqueous phase, forming a uniform, semi-transparent colloid. The circulation pump at the bottom of the vessel is started, and the temperature of the material in the reaction vessel is raised to 50°C using heat transfer oil or hot water in the jacket. A 15 wt% sodium hydroxide aqueous solution is slowly added dropwise to the vessel using a fully automatic feed pump at a rate controlled at 0.5 kg / min until the pH of the system stabilizes at 11.0~11.5. Maintaining this temperature and alkalinity, the in-situ stirring and activation reaction is continued for 45 min.

[0012] Maintaining the temperature inside the reactor at 50°C, 1.2 kg of 3-chloro-2-hydroxypropyltrimethylammonium chloride was added to the activated system in a single batch as a cationic etherification modifier. After the addition was complete, the stirring speed was increased to 250 rpm, and the system temperature was raised to 60°C. The reaction was carried out under this temperature field in a sealed environment for 3.5 hours.

[0013] After the reaction is complete, the jacket cooling water is turned on to cool the material in the reactor to below 30°C. The modified reaction solution is then pumped into an industrial membrane filter system with a molecular weight cutoff of 50-100 kDa for washing and filtration to remove the filtrate containing free byproduct sodium chloride and unreacted byproducts. Deionized water is continuously added until the conductivity of the discharged permeate drops below 50 μS / cm and the pH of the filtrate recovers to 7.0 ± 0.2.

[0014] The purified and washed modified nanocellulose concentrate was collected in a finished product mixing tank, and a paddle mixer was started. The solid content was quantitatively analyzed using an online rapid solids analyzer. Based on the test results, deionized water was added to adjust the final modified nanocellulose aqueous dispersion to 10.0 wt%. Finally, the mixture was filtered through a 150-mesh stainless steel pipe filter to obtain the modified nanocellulose aqueous dispersion for use in defoaming emulsion formulations.

[0015] Preferably, the mass ratio of terminal hydroxyl phenyl polysiloxane, tetramethyl dihydrosiloxane, anhydrous sodium acetate, allyl polyoxyethylene polyoxypropylene ether, platinum complex catalyst, dimethyl silicone oil, fumed silica, γ-glycidyl etheroxypropyltrimethoxysilane coupling agent, fatty alcohol polyoxyethylene ether AEO-3, deionized water, alkyl glycoside APG-0810, sodium metasilicate solid, and modified nanocellulose aqueous dispersion is 100.0:5.2:0.05:38.5:0.03:65.0:25.5:4.5:12.5:515.0:35.0:3.5:45.0. The present invention also provides a high-temperature resistant organosilicon defoaming emulsion for papermaking black liquor, prepared according to the above-mentioned production process. The defoaming emulsion is characterized by a median particle size (D50) of 1.8 μm to 2.5 μm, with droplet volume percentages greater than 4 μm being less than 3%, and an oil separation height of 0 mm to 0.15 mm after centrifugation. After standing for 12 hours under alkaline-thermal conditions at pH 13.5 and 130°C, it does not separate into layers and no silica precipitation is visible to the naked eye. In a 95°C original pulp black liquor system, its instantaneous defoaming time is 2.8 s to 5.2 s, the whiteness of the finished hand-made paper sheet is 76.2% to 79.2%, and the breaking length of the finished hand-made paper sheet is 4.12 km to 4.80 km.

[0016] The specific indicators of the high-temperature, alkali-resistant silicone defoaming emulsion for papermaking black liquor were obtained through the following test methods. The median particle size (D50) and particle size distribution were determined using a laser particle size analyzer, with the instrument preheated and background calibration completed. An appropriate amount of deionized water was injected into the sample cell as the dispersion medium, with the refractive index set to 1.333. 1.0 mL of the defoaming emulsion to be tested was pipetted and added dropwise to the sample cell until the light-blocking degree reached the test range of 10% to 15%. The circulating stirring system was turned on, with the speed set to 1200 rpm to avoid interference from sample air bubbles. The median particle size (D50) and the volume percentage of droplets larger than 4 μm were read and recorded on a volume basis. Each sample was measured in triplicate, and the average value was taken.

[0017] Measure 10.0 mL of the defoaming emulsion to be tested and inject it into a centrifuge tube, then place it symmetrically inside the centrifuge rotor. Set the centrifugation speed to 4000 rpm, the running time to 30 min, and the temperature to 25℃. After centrifugation, remove the centrifuge tube vertically and place it on a graduated rack. Observe and record quantitatively whether there is solid precipitate at the bottom of the tube, whether there is water separation in the middle, and whether there is an oil layer on the surface (height, unit: mm) by visual inspection and a ruler, thereby evaluating the centrifugation stability.

[0018] The test method for strong alkali thermal stability is as follows: 100.0 mL of defoaming emulsion is placed in a beaker. While stirring, 2.0 wt% sodium metasilicate aqueous solution and 1.0 mol / L sodium hydroxide solution are added dropwise alternately until the pH of the system stabilizes at 13.5. The prepared alkaline emulsion is then transferred to a polytetrafluoroethylene liner in a stainless steel high-pressure reactor, and the reactor lid is sealed. The high-pressure reactor is placed in an oven and heated to 130℃, then kept at this temperature for 12 hours. After the reaction is complete, the high-pressure reactor is removed and allowed to cool naturally to room temperature (25℃). The reactor lid is opened, and the emulsion is poured out. Its macroscopic morphology is observed under fluorescent light, and the presence of oil-water separation, surface silica precipitation, local clumping, or demulsification is recorded.

[0019] The operating procedure for the on-site performance test of black liquor is as follows: Raw black liquor discharged from the alkaline pulping process is introduced into the device. The basic physicochemical parameters of the black liquor are pH 13.2, dry weight content of 45% solids, and mainly composed of lignin and fatty acid soaps. A constant-temperature heat pump is turned on to circulate and heat the black liquor, maintaining its temperature at 95℃±1℃. An air pump is turned on to introduce air into the bottom of the circulation column at a constant flow rate of 2.5L / min, while simultaneously starting the circulation pump to circulate the black liquor, causing foam to rise rapidly. When the foam surface reaches the 800mL mark, a defoaming emulsion of 0.15wt% (based on the total mass of the circulating black liquor) is immediately injected into the center of the foam using a micropipette. Simultaneously, a stopwatch is started to record the time required for the foam to instantly drop from the 800mL mark to the initial liquid surface, recorded as the instantaneous defoaming time (s). After the instantaneous defoaming is completed, the air pump flow rate of 2.5L / min and the heat pump circulation state are kept constant, ensuring the system remains in a shear foaming state. Start the timer and record the time from when the foam is completely eliminated until the foam re-accumulates to the 800mL mark. This time is recorded as the sustained foam suppression time (min).

[0020] In addition, the following materials were used: Hydroxyphenyl polysiloxane with a purity ≥98.5% (IOTA 253); tetramethyldihydrosiloxane with a purity ≥99.0% (CAS 3277-26-7); anhydrous sodium acetate with a purity ≥99.0% (chemically pure or analytically pure crystalline powder, CAS 127-09-3); allyl polyoxyethylene polyoxypropylene ether with an average molecular weight of 800-1200 Da and an unsaturation degree ≥0.70 mmol / g (Guangdong Wengjiang Chemical Reagent Co., Ltd. PB93091); platinum complex catalyst (Karstedt platinum catalyst with an effective platinum mass fraction of 3000 ppm); dimethyl silicone oil (DOWSIL™ 200 Fluid (500 cSt); and fumed silica (AEROSIL® manufactured by Evonik Degussa). Type 200 fumed silica; γ-glycidyl etheroxypropyltrimethoxysilane coupling agent with a purity ≥98.0%, a molecular weight of 236.34, and a CAS number of 2530-83-8; fatty alcohol polyoxyethylene ether AEO-3 with a purity ≥99.0% and a hydroxyl value of 165-175 mg KOH / g; alkyl glycoside APG-0810 with the model number Glucopon® 215 UP; alkyl glycosides can also be selected from alkyl glycosides with a carbon chain length of C8-C14 or alkyl glycosides with a carbon chain length of C12-C14.

[0021] The modified nanocellulose aqueous dispersion has a solid content of 10.0% ± 0.5%, a crystal diameter of 4-10 nm, a length of 100-300 nm, and a CAS number of 9004-34-6. The nanocellulose raw material used is CelluForce NCC®, with a diameter of 4-10 nm, a length of 100-300 nm, and a solid content of 10.0%.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The organosilicon defoaming emulsion for papermaking black liquor exhibits excellent physicochemical stability and defoaming efficiency under high-temperature and strong alkaline conditions. By introducing phenyl groups into terminal hydroxyl phenyl polysiloxanes and combining this with a specific heat-preserving reaction, along with the introduction of polyether side chains and vacuum heat treatment using fumed silica coupling agents, the resistance of the active substrate to decomposition and the binding degree of the solid powder under alkaline and hot conditions are enhanced. After being kept at a constant temperature under strong alkaline and high-temperature conditions, the prepared emulsion remains in a homogeneous emulsion state without stratification or silica precipitation, demonstrating good physicochemical stability. In the original pulp black liquor system, it exhibits rapid instantaneous defoaming speed and long foam suppression time, improving the problem of defoamer easily breaking emulsions, precipitating silica, and becoming ineffective in the black liquor extraction stage.

[0023] 2. The defoaming emulsion uses a blend of alkyl glycosides and modified nanocellulose as the aqueous phase component, combined with a two-stage rate-controlled reverse phase reversal process and high-pressure homogenization, to achieve control over the emulsion particle size. It does not easily decompose in strongly alkaline hot water, thus maintaining a stable oil droplet morphology. Simultaneously, by adjusting the primary homogenization pressure, the median particle size of the emulsion is kept stable within the defoaming range, and the volume percentage of large-diameter droplets is low. This uniform particle size distribution suppresses aging and floating caused by the difference between gravity and buoyancy, avoiding oil drift and deterioration of defoaming activity due to excessive particle size caused by non-homogenization.

[0024] 3. In practical applications of the alkaline pulping post-treatment process, it has no impact on the final paper quality and exhibits good process compatibility. During the black liquor spraying and subsequent multi-stage extraction and refining stages, the defoaming emulsion maintains a stable oil droplet morphology and is removed during pulp washing, reducing the obstruction of the hydrophobic non-polar oil film to bleaching aids and the damage to inter-fiber bonding. Application results show that the paper sheets produced using the defoaming emulsion of this invention have normal blue light diffuse reflectance and whiteness values, and the breaking length meets industrial strength requirements. This is superior to the comparative groups where demulsification, hydrolysis, or excessive particle size led to reduced whiteness and deteriorated breaking length, demonstrating its ability to meet the requirements of continuous production in papermaking workshops. Attached Figure Description

[0025] Figure 1 This is a schematic diagram of the process flow and equipment flow of the present invention; Figure 2 This is a scatter plot of the fracture length of the handmade paper sheets from Examples 1-8 of the present invention. In the diagram: 1. Hydroxyphenyl polysiloxane feed line; 2. Tetramethyldihydrosiloxane feed line; 3. Anhydrous sodium acetate feed line; 4. Main reactor (oil phase synthesis and heat treatment reactor); 5. Anchor stirring system; 6. Reflux condenser; 7. Reflux control valve; 8. Vacuum system piping; 9. Jacketed heat transfer oil circulation pipeline; 10. Jacketed cooling water circulation pipeline; 11. Fumed silica batch intermittent feeding pipe; 12. Reactor bottom. 13. High-shear emulsifying pump; 14. Main feed line for aqueous phase raw materials (deionized water, alkyl glycosides, sodium metasilicate); 15. Auxiliary aqueous phase preparation vessel; 16. Aqueous phase conveying industrial metering pump; 17. Main pipeline for pre-emulsion conveying; 18. Two-stage high-pressure homogenizer; 19. Finished product compounding tank; 20. Feed line for modified nanocellulose aqueous dispersion; 21. Pipeline filter; 22. Finished product discharge line for organosilicon defoaming emulsion of high-temperature papermaking black liquor resistant to strong alkali. Detailed Implementation

[0026] The present invention will be further described in detail below with reference to the accompanying drawings. The present invention provides a production process for a high-temperature, alkali-resistant organosilicon defoaming emulsion for papermaking black liquor. The technical solution is as follows: See appendix Figure 1 The preparation of the defoaming emulsion in this invention is based on a production line with interconnected equipment. First, in the main reactor 4, terminal hydroxyl phenyl polysiloxane, tetramethyldihydrosiloxane, and anhydrous sodium acetate are quantitatively introduced through feed lines 1, 2, and 3, respectively. The anchor stirring system 5 is turned on, and the temperature is raised under the control of the jacketed heat transfer oil line 9. The reflux valve 7 is opened to allow the gas to flow back through the condenser 6. After the reaction is complete, the temperature is lowered, and fumed silica is intermittently drawn in through the suction pipe 11, along with a coupling agent. Then, the reflux valve 7 is closed, and the vacuum line 8 is turned on to perform high-temperature vacuum heat treatment on the silicone paste system. After the heat treatment is completed, a surfactant is added, and the high-shear emulsification pump 12 at the bottom of the reactor is started to construct a discharge recirculation loop to enhance shear. At the same time, in the auxiliary aqueous phase preparation vessel 14, the aqueous phase components are added through the main feed line 13 for stirring and dissolution. The prepared aqueous phase is pumped into the main reactor 4 through the aqueous phase delivery industrial metering pump 15 for reverse phase emulsification to obtain a pre-emulsion. Finally, the pre-emulsion is continuously pumped into a two-stage high-pressure homogenizer 17 via the main pipeline 16 for continuous multi-stage circulation homogenization. The refined emulsion is discharged into the finished product compounding tank 18 and mixed and stabilized by adding nanocellulose dropwise via the feed line 19. After being filtered and refined by the pipeline filter 20, the final product, a defoaming emulsion resistant to strong alkali and high temperature, is obtained from the finished product discharge line 21. A detailed description will follow with reference to specific examples.

[0027] Example 1

[0028] 100.0 kg of terminal hydroxyl phenyl polysiloxane was added to a reactor, followed by 5.2 kg of tetramethyldihydrosiloxane and 50 g of anhydrous sodium acetate. Stirring was started and the speed set to 70 rpm. Under a nitrogen atmosphere, the system was heated to 100 °C using jacketed heat transfer oil and refluxed for 180 min. After the reaction, the system was cooled to 78 °C. 20 mL of platinum complex catalyst was added to the reactor, and the temperature was controlled at 90 °C using jacketed cooling water. Then, 38.5 kg of allyl polyoxyethylene polyoxypropylene ether was added dropwise at a rate of 100 g / min, maintaining the reactor temperature below 110 °C. The remaining 10 mL of platinum complex catalyst was added, and the reaction was maintained at 100 °C for 4 h. The temperature was then lowered to 55 °C to obtain a liquid mixture of side-chain polyether and phenyl-modified polysiloxane, which remained directly in the original reactor. The condenser was kept unobstructed during the reaction, and the generated gas was collected and discharged through an exhaust pipe.

[0029] Add 65.0 kg of dimethyl silicone oil to the above liquid, start the anchor stirrer and set the speed to 75 rpm, and heat the system to 120°C. Maintain the vacuum level inside the reactor at -0.05 MPa for 30 minutes. Introduce 25.5 kg of fumed silica in three batches of 8.5 kg each through the suction pipe, stirring intermittently for 8 minutes after each batch. Then increase the stirring speed to 120 rpm, add 4.5 kg of γ-glycidyl etheroxypropyltrimethoxysilane coupling agent to the system, close the reflux valve and start the vacuum system, maintaining the vacuum level inside the reactor at -0.085 MPa. Heat to 162°C and react for 3.5 hours. After the reaction is complete, cool the system to 65°C.

[0030] Add 12.5 kg of fatty alcohol polyoxyethylene ether AEO-3 directly, start the high-shear emulsification pump at the bottom of the reactor, set the shear speed to 2900 rpm, and circulate the shear for 20 minutes. In another 1000 L auxiliary aqueous phase reactor, add 515.0 L of deionized water, along with 35.0 kg of alkyl glycoside APG-0810 (50% solid content) and 3.5 kg of sodium metasilicate solid, and stir and heat to 60 °C until completely dissolved. Maintain the temperature inside the main reactor at 65 °C, and start the anchor stirrer at 100 rpm and the high-shear pump at the bottom of the reactor at 2500 rpm. During the first stage of water addition, pump 20% of the total prepared aqueous phase, i.e., 110.7 L, into the oil phase reactor using an industrial metering pump at a rate of 3.5 kg / min. During the second stage of water addition, while maintaining the stirring and shear speeds, pump the remaining 80% of the aqueous phase, i.e., 442.8 L, at a rate of 9.5 kg / min; after all the aqueous phase has been added, continue high-shear circulation for 15 minutes. Subsequently, the pre-emulsion was directly pumped into an industrial two-stage high-pressure homogenizer. The first-stage homogenization pressure was set to 350 bar, and the second-stage homogenization pressure was set to 60 bar, with continuous homogenization cycles repeated twice. The median particle size (D50) of the emulsion, measured by an online particle size analyzer, was 1.8 μm to 2.5 μm, and the volume percentage of droplets larger than 4 μm was less than 3%. Finally, the homogenized emulsion was discharged into a finished product tank, and 45.0 kg of modified nanocellulose aqueous dispersion with a solid content of 10% was added. The mixture was stirred at 60 rpm for 30 min. After the system was cooled to below 35°C, it was filtered through a 100-mesh pipeline filter to obtain a silicone defoaming emulsion for papermaking black liquor.

[0031] To investigate the effects of different process conditions on the performance of the final papermaking black liquor silicone defoaming emulsion, the parameters of Examples 2-8 are listed in Table 1.

[0032] Table 1

[0033] The comparative examples were set up based on Example 1, and the masses of substances not added in the comparative examples were made up with blank deionized water.

[0034] Comparative Example 1: 100.0 kg of terminal hydroxyl phenyl polysiloxane, 5.2 kg of tetramethyldihydrosiloxane, and 50 g of anhydrous sodium acetate were refluxed at 100 °C for 180 min. After the reaction, the temperature was lowered to 55 °C, without adding 38.5 kg of allyl polyoxyethylene polyoxypropylene ether or 30 mL of platinum complex catalyst.

[0035] Comparative Example 2: After preparing the modified polysiloxane according to the procedure in Example 1, 65.0 kg of dimethyl silicone oil was added, and under a vacuum of -0.05 MPa at 120°C, 25.5 kg of fumed silica was introduced in three batches of 8.5 kg each over 30 min, with intermittent stirring for 8 min. The rotation speed was increased to 120 rpm, without adding 4.5 kg of γ-glycidoxypropyltrimethoxysilane coupling agent. The vacuum system was directly turned on, and the reaction was carried out at 162°C for 3.5 h.

[0036] Comparative Example 3: The oil phase and AEO-3 were prepared following the steps in Example 1. In the auxiliary aqueous phase reactor, instead of adding 35.0 kg of alkyl glycoside APG-0810 with a solid content of 50%, 35.0 kg of nonionic surfactant Tween-80 was used.

[0037] Comparative Example 4 used the formulation of Example 1 and a two-stage reverse phase water addition emulsification process. The water addition rate was 3.5 kg / min in the first stage and 9.5 kg / min in the second stage. After the water addition was completed, high-shear cycling was continued for 15 min. After pre-emulsification, the pre-emulsion was directly discharged into the finished product tank without homogenization, and 45.0 kg of modified nanocellulose aqueous dispersion was added for medium-speed stirring.

[0038] The above samples were subjected to basic physicochemical property tests and strong alkali thermal stability tests. The test results are shown in Table 2.

[0039] Table 2

[0040] As shown in Table 2, the steric hindrance of the phenyl group in the active component of the examples provides heat resistance, and the added polyether side chain constructs an intramolecular amphiphilic balance, thereby enabling the defoaming emulsion to have stable defoaming and foam-suppressing performance in the high-temperature and strong alkaline environment of papermaking black liquor. In Comparative Example 1, the lack of added polyether side chain resulted in the active component being difficult to disperse uniformly in water, directly causing demulsification and stratification with large oil spots in the high-temperature and strong alkaline test. By adding a silane coupling agent and subjecting the fumed silica to vacuum heat treatment at 162℃, the bonding between the solid powder and silicone oil was enhanced. In Comparative Example 2, the lack of a coupling agent caused the solid powder to easily detach from the silicone oil under alkaline and hot conditions, resulting in poor dispersion stability and rapid loss of long-term foam-suppressing ability of the defoamer, shortening the defoaming time. The use of alkyl glycosides and modified nanocellulose as the aqueous phase component resulted in less decomposition in strongly alkaline hot water, maintaining a stable oil droplet morphology, while the comparative example... In Example 3, Tween-80 underwent chemical hydrolysis at high temperature and strong alkali conditions, resulting in complete stratification of the finished product within a few hours. Through a two-stage controlled-rate reverse phase reversal and high-pressure homogenization process, the median particle size D50 of the emulsion was controlled within the range of 1.8 μm to 2.5 μm. In contrast, in Comparative Example 4, the median particle size increased to 8.4 μm due to the absence of a high-pressure homogenizer pulverization process, with coarse droplets larger than 4 μm accounting for as much as 24.3%. Under the influence of gravity and buoyancy, the emulsion rapidly floated to the surface, and in the black liquor test, the excessively large droplets could not effectively eliminate foam, extending the instantaneous defoaming time to 18.2 s.

[0041] The black liquor from the alkaline pulping process is sent to the multi-stage extraction system in the workshop. At this point, the black liquor has a pH of 13.2, a temperature of 115℃, and contains 45% lignin and fatty acid soaps in its dry weight. The produced silicone defoaming emulsion is injected into the outlet pipeline of the cooking waste liquor spray chamber via an industrial metering pump. Based on the pulp flow rate, the continuous injection rate of the metering pump is controlled at 6.25 kg / h, and the amount of silicone defoaming emulsion added is 1.5 kg per ton of pulp. The black liquor mixture flows through a first-stage extrusion decomposer with a screw compression ratio of 4.5:1, and enters a first-stage preimpregnation tank, where it is held at 90℃ for 40 minutes. It then passes through a second-stage extrusion decomposer with a screw compression ratio of 4.5:1. In the second-stage preimpregnation tank, hydrogen peroxide (2.5% of oven-dry pulp mass), ethylenediaminetetraacetic acid (0.15%), and magnesium sulfate (0.05%) are added, and the mixture is impregnated at 85℃ for 30 minutes. The pulp then passed sequentially through a high-consistency refiner and a low-consistency refiner. The high-consistency refiner had a disc gap of 1.2 mm, a pulp concentration of 28%, and fiber length decreased from 2.1 mm to 1.5 mm. The low-consistency refiner had a disc gap of 0.25 mm, a pulp concentration of 12%, and pulp specific surface area decreased from 2.8 m² / s². 2 / g increased to 6.5m 2 / g; Finally, the slurry was treated for 40 minutes at a concentration of 4% and a temperature of 95℃, mechanically screened through a 0.15mm slotted screen, dewatered to a concentration of 30%, and then sent to a PFI mill for pulping. The pulping concentration was set at 10% and the pulping degree was 28°SR to 32°SR. After pulping, the slurry was made into sheet by hand.

[0042] The hand-made sheets obtained after applying the defoamers of each embodiment or comparative example were equilibrated in a constant temperature and humidity chamber at 23℃±1℃ and 50%±2% relative humidity for 24 hours. The hand-made sheets were cut into 60mm×60mm square samples, stacked in 5 layers until opaque. A whiteness meter was turned on and calibrated using a standard white plate in a dual-channel configuration. The samples were placed flat on the test holes, and the blue light diffuse reflectance factor R of the front and back sides of the hand-made sheets was measured according to GB / T 7974-2013. 457 Whiteness value. Five parallel measurements were taken for each sample, and the arithmetic mean was used. After being equilibrated under constant temperature and humidity, the hand-coated sheet was cut into strips with a width of 15.0 mm and a length of not less than 150 mm using a standard strip cutter. The upper and lower clamps of the tensile strength testing machine were set to a distance of 100 mm, and the tensile speed to 20 mm / min. The strips were vertically clamped in the clamps, and the instrument was started to stretch the strip until it broke. The breaking load F (in N) and the quantitative weight (in g / m³) were recorded. 2 The fracture length L, in km, was calculated based on the tensile strength conversion standard GB / T 12914-2018. Tensile strength was measured in 10 longitudinal specimens for each sample, and the average value was taken. The results are shown in Table 3 and... Figure 2 As shown.

[0043] Table 3

[0044] The above test results show that the alkaline pulping black liquor system has strict requirements for the stability of the defoaming emulsion, which directly affects subsequent bleaching and paper forming. In Examples 1-8, since all conditions were within the optimized range, the emulsions showed strong resistance to decomposition in pulp at 95℃ and pH 13.2, and no micro-droplet demulsification occurred. Figure 2The paper sheet from Example 7 exhibited the highest breaking length. During subsequent hydrogen peroxide alkaline bleaching, no free silicone oil adhered to the cellulose surface, the bleaching agent was uniformly impregnated, and the paper whiteness ranged from 76.2% to 79.2%. Simultaneously, the stable oil droplet morphology was removed during pulping, preventing the hydrophobic nonpolar oil film from blocking the formation of interfiber hydrogen bonds, resulting in a breaking length of 4.12 km to 4.80 km. Comparative Example 1, lacking polyether side chains, experienced large-scale demulsification, with free silicone oil spots adhering to the fiber surface, hindering bleaching and encapsulating the fibers, leading to a decrease in whiteness to 68.3% and a breaking length reduced to 2.54 km. Comparative Example 2, lacking heat treatment coupling anchoring, experienced powder desorption and dissolution under strong shear, with silicone oil agglomeration and floating causing yellowing, resulting in a whiteness reduction to 72.1% and a breaking length reduced to 3.10 km due to residual oil contamination. In Comparative Example 3, Tween-80 under strong alkali conditions underwent hydrolysis, causing the emulsion to completely separate into layers. The free components attached to the active sites of the fiber hydrogen bonds, resulting in a deterioration in whiteness and breaking length. In Comparative Example 4, the lack of high-pressure homogenization led to an excessive median particle size. Coarse droplets rapidly floated to the surface under shear and gravity, creating localized hydrophobic voids during papermaking, resulting in a whiteness of only 69.8% and a breaking length reduced to 2.88 km.

[0045] It should be understood that although the invention has been described in conjunction with specific embodiments, the foregoing description is intended to illustrate and not limit the scope of the invention, which is defined by the appended claims. Other embodiments, advantages, and modifications are within the scope of the following claims. It should be understood that other embodiments and changes may be utilized without departing from the scope of the invention.

Claims

1. A production process for a high-temperature, alkali-resistant organosilicon defoaming emulsion for papermaking black liquor, characterized in that, The production process includes reflux of hydroxyl-terminated phenyl polysiloxane, tetramethyl dihydrosiloxane and anhydrous sodium acetate, cooling and adding allyl polyoxyethylene polyoxypropylene ether dropwise to react with a catalyst; adding dimethyl silicone oil, fumed silica and coupling agent for vacuum heat treatment; adding fatty alcohol polyoxyethylene ether to obtain an oil phase, and adding water to the aqueous phase with alkyl glycosides and sodium metasilicate, and mixing in modified nanocellulose; The modified nanocellulose was obtained by treatment with 3-chloro-2-hydroxypropyltrimethylammonium chloride.

2. The production process of the high-temperature, alkali-resistant organosilicon defoaming emulsion for papermaking black liquor according to claim 1, characterized in that, By mass, the terminal hydroxyphenyl polysiloxane comprises 100 parts, the tetramethyldihydrosiloxane comprises 5.2 parts, the allyl polyoxyethylene polyoxypropylene ether comprises 38.5 parts, the dimethyl silicone oil comprises 65 parts, the fumed silica comprises 25.5 parts, the alkyl glycoside comprises 35.0 parts, and the sodium metasilicate comprises 3.5 parts.

3. The production process of the high-temperature, alkali-resistant organosilicon defoaming emulsion for papermaking black liquor according to claim 1 or 2, characterized in that, Before the vacuum heat treatment, the temperature is controlled at 115℃-125℃ and the vacuum degree is -0.045MPa to -0.055MPa. The fumed silica is drawn in in 3 batches, with each batch intermittently stirred for 7min-9min.

4. The production process of the high-temperature, alkali-resistant organosilicon defoaming emulsion for papermaking black liquor according to claim 1, characterized in that, The aqueous phase is added to the water, and the temperature is controlled at 60℃-70℃. In the first stage, 20% of the total aqueous phase is added by pumping water in at a rate of 3.2kg / min-3.8kg / min. In the second stage, the remaining 80% of the aqueous phase is added by pumping water in at a rate of 6.0kg / min-13.2kg / min. After the addition is completed, shearing circulation is performed for 12min-18min.

5. The production process of the high-temperature, alkali-resistant organosilicon defoaming emulsion for papermaking black liquor according to claim 1, characterized in that, The alkyl group in the alkyl glycoside has a carbon chain length of C8-C10.

6. The production process of the high-temperature, alkali-resistant organosilicon defoaming emulsion for papermaking black liquor according to claim 1, characterized in that, Before being mixed with the modified nanocellulose, the mixture is homogenized. The first homogenization pressure is 260 bar-470 bar, the second homogenization pressure is 55 bar-65 bar, and the homogenization is repeated twice.

7. The production process of the high-temperature, alkali-resistant organosilicon defoaming emulsion for papermaking black liquor according to claim 6, characterized in that, The modified nanocellulose is prepared as follows: the unmodified nanocellulose crystal aqueous dispersion is diluted with water, heated to 50°C, and sodium hydroxide aqueous solution is added dropwise to adjust the pH value to 11.0-11.5; the 3-chloro-2-hydroxypropyltrimethylammonium chloride is added, and the reaction is carried out at 60°C for 3.5 h; the membrane module is used to wash the permeate until the conductivity drops below 50 μS / cm and the pH value is 7.0±0.2; the solid content is adjusted to 10.0 wt% and filtered to obtain the modified nanocellulose.